Proposta metodológica de revisão sistemática: um estudo a partir de fundamentos da Biblioteconomia e da Ciência da Informação - Graciane Silva Bruzinga Borges (2020)
The Literature Review (LR) is the procedure through which the researcher acquires knowledge about his object of study. At this point of the research correlated studies are identified, and it is possible to avoid the repetition of conclusions already disclosed. The Systematic Literature Review (SLR) is a specific LR technique. It solves discrepancies between studies and enables the analysis and use of quality information, as well as supporting evidence-based practice and decision-making. However, the SLR process may present weaknesses, such as (1) little orientation to the review issue, (2) lack of planning, (3) insufficient research strategies, and (4) interpretation of the results and writing of the superficial report. This research investigated the theoretical and methodological contributions of Librarianship and Information Science (LIS) for modeling an SLR. The objective is to develop a proposal for a systematic review focused on multiple areas of knowledge and with a high degree of detail of the activities of bibliographical research and writing. The methodology was composed of the comparative method and involved practical, descriptive procedures with a qualitative approach to the analysis of the specialized literature of the area. The methodological path was based on two stages. In the First Stage, there was a literature review of the thesis, which aimed to know methodologies, national and international on the preparation of the SLR. This step was performed in three phases: (1) planning the review, (2) presentation of the included studies, and (3) discussion of the review. For this, we used the systematic method without meta-analysis, conducted according to the Cochrane Recommendations in an adapted way, which allowed the specification of 22 SLR proposals and 32 bibliographic data processing software. The analyses showed that the review provided inputs for the design of version 1 of the prototype Systematic Literature Review based on Structured Bibliographic Research (RSL-PBE). The Second Stage included the design and validation test of version 1 of the RSL-PBE Prototype carried out in a master’s degree in the healthcare field. This step was performed in three phases: (1) solution outline, (2) solution application, and (3) solution discussion. Its application indicated that the proposal consistently mapped the literature with breadth. So, to validate this proposal, a semi-structured interview was applied with the author of the master’s research, which revealed that the adoption of the first version of the prototype, in that research, answered the review question clearly and strengthened its theoretical-methodological framework. The results culminated in the conception of version 2 of the RSL-PBE Prototype, containing four procedural modules (1. Planning; 2. Review Question; 3. Bibliographic Research and 4. Discussion and Writing), which are subdivided into 14 sequential steps and 63 execution steps.